Qawaid Tafsir: Analysis of the Application of Mutaradif Lafadz Turᾱb, Thin, Shalsalᾱ, and Fakhkhar (Study of M. Quraish Shihab's Interpretation) - Intan Dwi Andari; Ahmad Isnaeni; Budimansyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The issue of mutarādif (synonymy) is a subject of debate among scholars; some acknowledge its existence in language and its potential occurrence in the Qur'an, while others deny it. Nevertheless, some scholars adopt a cautious approach when interpreting mutarādif terms within the Qur'an. Furthermore, the Qur'an extensively discusses human beings and the mysteries of their lives across all related aspects—such as the creation of humanity. In this context, several verses employ terms like turāb, ṭīn, ṣalṣāl, and fakhkhār. Consequently, the author will focus on the exegetical principles regarding the synonymous terms turāb, ṭīn, ṣalṣāl, and fakhkhār (specifically according to the interpretation of M. Quraish Shihab). While M. Quraish Shihab acknowledges that turāb, ṭīn, ṣalṣāl, and fakhkhār appear to be synonyms denoting